Untitled. (El Idealismo Sintético de Juan Valera, 1990)
A list of several publications submitted to Scripta Humanistica along with its prices is presented which includes "Collapse and Reorganization of the Latin Nominal Flection as Reflected in Epigraphic Sources," by Paul A. Gaeng, "Out of Bounds," by Elizabeth Sullam, and "Spanish Grammar and Culture Through Proverbs," by Richard D. Woods.